EFEKTIVITAS PEMUTUSAN MULTIWALLED CARBON NANOTUBES (MWNT) DENGAN MENGGUNAKAN HIGH ENERGY MILLING DAN CONVENTIONAL BALL MILLING - Nono Darsono (Widyariset, 2009)
The cutting efficiency of MWNTs was compared systematically between conventional ball milling and high-energy milling. The efficiency of both processes was evaluated in term of dispersion properties, aggregates size evolution, and degree of crystallinity. Two-hour high-energy milling produced a large portion of MWNTs smaller than 150 nm, while even 120-hour ball milling struggled to achieve smaller than 300 nm. It was revealed by the significantly viscosity value. Since the high-energy milling viscosity was much higher than ball milling, 2-hours high energy milling exhibited lower damage on the MWNTs thread than the 120-hours ball milling according to the I /I ratio and values of raman spectra were 3.63 and 2.81 for high energy milled and ball milled respectively.